INDOOR SMARTPHONE LOCALIZATION USING WLAN - Muzaky Dwi Putra, Faishol
Around 80-90% of smartphone users spend their time indoors carrying out various daily activities such as working, playing, shopping, and communicating so that will become a problem that can disrupt daily activities if someone loses their cell phone. Therefore, we need a system that can track the location of cell phones in the room. Currently, Global Positioning System (GPS) technology is most often used to determine the location of a smartphone. However, the use of GPS for location tracking systems can only work optimally in outdoor conditions. In indoor conditions, the GPS signal strength is unable to penetrate the walls of buildings, as a result, the GPS signal cannot spread evenly and there is a decrease in signal strength, deflection, and reflection of the GPS signal. The purpose of this study is to build a mobile application that can accurately track the location of a cell phone indoors using a fingerprint method based on a Wireless Local Area Network (WLAN) signal and determine the effect of the Kalman Filter algorithm on RSSI measurements on the accuracy of the cell phone tracking system indoors. The results of the test show that the RSSI value using the Kalman Filter obtains an accuracy rate of 85% for k = 5 while the RSSI value without using the Kalman Filter obtains an accuracy rate of 85% for k = 3, and the application of the Kalman Filter algorithm to the measurement of the RSSI value proven capable of increasing the accuracy of RSSI measurements but unable to improve the accuracy of cell phone tracking indoors.